Cake Time - Ju, Siel (Book collections on Project MUSE., 2017)
"Daring yet aimless, smart but slightly strange, Cake Time's young female protagonist keeps making slippery choices, sliding into the dangerous space where curiosity melds with fear and desires turn into dirty messes. In "How Not to Have an Abortion," the teenaged narrator looks for a ride from the clinic between her AP exams. In "Easy Target," the now-college-grad agrees to go to a swingers party with a handsome stranger. A decade later, in "Glow," she is suddenly confronted by the disturbing and thrilling fact of her lover's secret daughter."--Back cover.